RELATIONSHIP OF SELF-ESTEEM TO POSTPARTUM DEPRESSION IN POSTPARTUM MOTHERS - Vina Ayu Wardani; Kustati Budi Lestari; Irma Nurbaeti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Self-esteem influences women's transition to a new identity and adjustment of motherhood. Mothers with low self-esteem have poor coping, so it is easy to experience depression. In the postpartum period, physiological changes and psychological changes can trigger anxiety and depression that affect the bonding of the baby and mother. The purpose of this study was to find out if there was a link between self-esteem and postpartum depression. Method Quantitative research with cross-sectional design against 287 postpartum mothers 1-12 months meets inclusion criteria. Collection of research data in March – June 2016 in the working area of Puskesmas Ciputat Timur and Ciputat Tangerang Selatan; and Kebayoran Lama and Cilandak Jakarta Selatan. The research instrument uses the Indonesian version of the Edinburgh postpartum depression scale to measure postpartum depression and Rosenberg Self-Esteem Scale in Bahasa Indonesia to measure postpartum maternal self-esteem. Data collection with home visits. Test the statistic using Chi-square with α=0.05. The results showed that of the 38% of mothers with low self-esteem, 11.5% had postpartum depression. The chi-square test analysis results have a relationship between self-esteem and postpartum depression (p=0.002 value). Conclusion mothers with low self-esteem are at higher risk of causing postpartum depression, so it is necessary to increase postpartum mothers' self-esteem to undergo a transition period happily.